The complete chloroplast genome sequence of Liparis yongnoana, an endemic orchid of Korea. Issue 2 (3rd July 2019) - Ha, Young-Ho; Gil, Hee-Young; Lee, Jungsim; Kim, Dong Kap; Choi, Kyung; Chang, Kae Sun; Oh, Seung-Hwan
Abstract: The complete chloroplast genome sequence of Liparis yongnoana was determined and analyzed in this study. The chloroplast genome size is 153, 165 bp in length with 36.9% GC content. It comprises a large single-copy region (LSC) of 83, 690 bp, a small single copy region (SSC) of 17, 661 bp, and a pair of inverted repeat regions (IRa and IRb) of 25, 907 bp separated by the SSC. The genome contains 132 genes, including 86 protein-coding, eight ribosomal RNA, and 38 transfer RNA genes. Phylogenetic analysis inferred from 16 Orchidaceae chloroplast genomes suggested that L. yongnoana was closely related to L. loeselii .